2017
DOI: 10.1002/ece3.2808
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific floral morphology, biomass, and phytohormones associated with altitude in dioecious Populus cathayana populations

Abstract: Relationships between sex‐specific floral traits and endogenous phytohormones associated with altitude are unknown particularly in dioecious trees. We thus examined the relationships between floral morphology or biomass and phytohormones in male and female flowers of dioecious Populus cathayana populations along an altitudinal gradient (1,500, 1,600, and 1,700 m above sea level) in the Xiaowutai Nature Reserve in northern China. The female and male flowers had the most stigma and pollen at 1,700 m, the largest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…In poplars (Populus sp. ), the males exhibited a smaller decrease in leaf IAA than females following a short-day shift [84], although the concentration of IAA was higher in the female flowers than in the male flowers [85]. In the current study, the levels of IAA in the 5-azaC-treated plants were significantly lower than the controls but the IAA levels in both the treated and control plants declined from the flower transition stage to the flower development stage (Figure 3a,b).…”
Section: The Relationship Between Endogenous Carbohydrates Hormones supporting
confidence: 38%
“…In poplars (Populus sp. ), the males exhibited a smaller decrease in leaf IAA than females following a short-day shift [84], although the concentration of IAA was higher in the female flowers than in the male flowers [85]. In the current study, the levels of IAA in the 5-azaC-treated plants were significantly lower than the controls but the IAA levels in both the treated and control plants declined from the flower transition stage to the flower development stage (Figure 3a,b).…”
Section: The Relationship Between Endogenous Carbohydrates Hormones supporting
confidence: 38%
“…This could be interpreted as willows at high altitude may be more adaptable to stress environment for they are exposed to harsher conditions (including extremely lower temperature, drier, and stronger ultraviolet radiation) for a long period. Males and females from different altitude might have different evolution speed with long‐term various environmental stresses, which lead to amplify or reduce the sexual difference and different sex‐related responses to stress environment (He et al, ; Huang et al, ). As to the reason why drought tolerance between sexes differed among different altitude, perhaps because the high variance between clones might musk the true sex‐related effects responding to drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on Populus cathayana , a male‐biased alpine tree, have shown that male individuals are more tolerant to drought stress than females because of their higher values of total chlorophyll concentration, net photosynthetic rate, activities of superoxide dismutase, peroxidase, and less negative effects on cellular membranes and chloroplasts (Chen, Duan, Wang, Korpelainen, & Li, ; He et al, ; Xu, Peng, Wu, Korpelainen, & Li, ; Xu, Yang, et al, ; Zhang et al, , Zhang, Jiang, Zhao, Korpelainen, & Li, ). However, in the genus Salix , female individuals occurred more frequently than males in their natural habitats (Dawson & Bliss, ; Dudley, ; Hughes et al, ; Ueno, Suyama, & Seiwa, ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher temperature results in an increase in the number of male flowers (Sage et al 2015), whereas elevated CO 2 results in the production of more female-biased progeny in Silene latifolia cv Poiret (Wang 2005); higher C/N ratio promotes male tendency while lower C/N ratio inhibits male flower development in bitter melon (Momordica charantia L.) due to its mediating role in the production of gibberellic acid, indole acetic acid, and dihydrozeatin which all have positive influence on flower formation (Kossuth and Ross 1987;Wang et al 2001;Talamali et al 2003;Glawe and Jong 2005). These studies indicate that sex differentiation in flowers is determined not only by genotype and phytohormones but also by C/N ratio and environmental factors (Yamasaki et al 2000;Wang et al 2001;Deputy et al 2002;Khryanin 2002;Wu et al 2010;Gerashchenkov and Rozhnova 2013;He et al 2017).…”
Section: Introductionmentioning
confidence: 84%